2012
DOI: 10.1161/strokeaha.111.630384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thrombolysis on Stroke Outcome at 12 Months in a Population

Abstract: for the QABE investigatorsBackground and Purpose-Thrombolysis improves outcome of patients with acute ischemic stroke, but it is unknown whether thrombolysis has a measurable effect on long-term outcome in a defined population. Methods-We prospectively assessed demographic data, management, and outcome of acute ischemic stroke patients admitted within 48 hours to 18 primary care hospitals of the canton of Bern (969 299 inhabitants) during 12 months. Blinded follow-up was obtained at 3 and 12 months. Predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 30 publications
(19 reference statements)
7
28
0
Order By: Relevance
“…Classically, NIHSS has been described as an independent predictor of clinical improvement after recanalization therapies [11][12][13] and a long term clinical outcome predictor [14]. In previous studies, NIHSS values have consistently been demonstrated to be lower in DR patients, [2,4,5] and clinical severity in our study population was similar to these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Classically, NIHSS has been described as an independent predictor of clinical improvement after recanalization therapies [11][12][13] and a long term clinical outcome predictor [14]. In previous studies, NIHSS values have consistently been demonstrated to be lower in DR patients, [2,4,5] and clinical severity in our study population was similar to these studies.…”
Section: Discussionsupporting
confidence: 88%
“…In ten (17.5%) patients, no 26,27 . Consequently, as the cost-effectiveness of the initial treatment 2,20,21 and PSC for acute stroke care has been reported, it would be logical to invest money in the first steps of the curative treatment, which remains challenging when financial resources may be lacking 28 .…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, considering the patients in this study as a whole, we observed further significant clinical improvement between 3-month and 1-year FU, whereas natural stroke history without treatment suggests stable clinical outcome over time. 19 This suggests that clinical evaluation would be more appropriate at 1 or 2 years rather than at 3 months.…”
Section: Discussionmentioning
confidence: 99%